CADMIUM CHLORIDE INDUCED DOSE AND DURATION DEPENDENT BIOMASS VARIATION IN NOSTOC PUNCTIFORME Ag. IN CULTURE - RANI, NEETA; RAIPAT, BHARTI; SHARAN, LATIKA (The Bioscan, 2007)
Bioaugmentation is one of the essential components of bioremediation, a biotechnological method of recent origin. Bioaugmentation is the process of introducing a known veriety of bioremedial agent into contaminated environment to initiate and sustain a specific bioremedial process. The paper deals with the biomass production of Nostoc punctiforme under the influence of different concentrations of cadmium chloride in laboratory culture. The success of bioremedial process by N. punctiforme depends upon its biomass production, which in due course removes the heavy metal.In control culture the biomass of N. punctiforme as mg /50ml varied from 13.79 (0 day) to 22.88(25th day). The corresponding values for 0.01 and 0.5 ppm cadmium chloride treatment after 25 days were 20.68, 14.98 and 10.01 mg/50ml respectively, indicating a decline in biomass of N. punctiforme with increase in concentration. A two way ANOVA revealed the variation of biomass with respect to concentration and duration of treatment statistically significant (F= 10.494, df5,3; p<0.001 and F= 20.004, df 5,3; p<0.001). The results indicate better perfomance of N. punctiforme at lower concentrations.